1996
DOI: 10.1038/ki.1996.403
|View full text |Cite
|
Sign up to set email alerts
|

ESRD patient mortality with adjustment for comorbid conditions in Lombardy (Italy) versus the United States

Abstract: The present study evaluated end-stage renal disease (ESRD) patient survival in Lombardy, Italy, and the United States (U.S.) using data from two registries, the Lombardy Dialysis and Transplant Registry (RLDT) and the U.S. Renal Data System (USRDS), respectively. For this purpose, 4,196 white patients (2,900 from the USRDS Case Mix Severity Study and all 1296 from RLDT) who started renal replacement therapy in 1986 and 1987 were studied. Compared to Lombardy patients, those in the USA were significantly older … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
1
3

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(93 citation statements)
references
References 9 publications
3
86
1
3
Order By: Relevance
“…Esse fato, que corresponde também aos registros mundiais de diálise 4,5 , impulsionou o interesse em se constatar o nível de qualidade de vida oferecida pela terapia hemodialítica, sendo essa medida cada vez mais recomendada como parâmetro a ser monitorizado regularmente. Além disso, tem crescido a importância do nível de qualidade de vida como fator prognóstico de desfechos clínicos insatisfatórios tais como: mortalidade, número de internações, falta de adesão à terapia hemodialítica 6 .…”
Section: Introductionunclassified
“…Esse fato, que corresponde também aos registros mundiais de diálise 4,5 , impulsionou o interesse em se constatar o nível de qualidade de vida oferecida pela terapia hemodialítica, sendo essa medida cada vez mais recomendada como parâmetro a ser monitorizado regularmente. Além disso, tem crescido a importância do nível de qualidade de vida como fator prognóstico de desfechos clínicos insatisfatórios tais como: mortalidade, número de internações, falta de adesão à terapia hemodialítica 6 .…”
Section: Introductionunclassified
“…[6][7][8][9][10][11][12][13][14] Recent studies have shown that HCV is an important cause of morbidity and mortality in chronic dialysis patients. [15][16][17][18][19] Interferon-based therapy is the mainstay of therapy for HCV-related liver disease. Its use is not recommended after renal transplantation due to a significant risk of graft loss.…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons of hemodialysis outcomes across distinct geographic regions have helped to elucidate the determinants of these country-specific variations (6)(7)(8). The Dialysis Outcomes and Practice Patterns Study (DOPPS) revealed that differences in country-specific mortality rates persist after comprehensive adjustment for demographics, comorbid conditions and other case-mix variables (8).…”
Section: Introductionmentioning
confidence: 99%